Factors contributing towards malnutrition among under five indigenous children: a systematic review - Zakaria, Liyanatul Najwa; Minhat, Halimatus Sakdiah; Mohd Zulkefli, Nor Afiah; Baharom, Anisah; Ahmad, Norliza (Indian Society for Education and Environment, 2019)
Objectives: To identify and synthesize the evidences regarding factors contributing towards malnutrition among fewer than five indigenous children. Methodology: A systematic review was conducted using electronic databases by searching published articles earliest from January 2000 to April 2017 using five different data bases including MEDLINE, PubMed, Scopus, Proquest and CINAHL. Literatures that provide information on factors contributing towards malnutrition among fewer than five indigenous children according to type of malnutrition (stunting, wasting and underweight) were included. A narrative synthesis was used. Findings: Nine studies were assessed and reviewed in the final stage. This review found that malnutrition among fewer than five indigenous populations is a multifactorial problem and that different domain play in the pathway. These mainly include socioeconomic status, parental factor, and child factor, hygiene and child morbidity as the most common and significant factors contributing towards malnutrition among under five indigenous children. Novelty/ Improvement: Identification of appropriate and relevant factors contributing towards malnutrition problem among fewer than five indigenous populations is important to develop a well-planned and ensuring the effectiveness of health intervention.